Relationship Between The Location Of Benign Vocal Cord Lesion And The Degree Of Voice Handicap Index-30 - Lisa Apri Yanti; Irfannuddin Irfannuddin; Nilam Kusuma Anggraeni (Biomedical Journal of Indonesia, 2023)
Introduction. Voice disorder or dysphonia is a condition that includes all changes in a person’s voice including tone, intensity, phonation, and others caused by laryngeal disorders. Each sound production disorder can be evaluated through the VHI-30 questionnaire. Therefore, data are needed regarding the relationship of the extent of the lesion location site to the degree of VHI-30 produced in dysphonic patients with benign vocal cord lesions. Methods. Observational research using cross sectional design. Data collection using medical record data on 30 dysphonic patients with benign vocal cord lesions who underwent surgery in the ENT department in RSMH in January 2019 to June 2022. Results. Out of the 30 patients with benign vocal cord lesions, age of 31-45 and 46-60 age groups were most found 11(36,7%) Female gender was found 16(53,3%) and the non-professional voice user category was found the highest 28 (93,3%). The 1–6-month onset group was the highest 12(40,0%). The most common location of benign vocal cord lesions was in 1/3 anterior 8(26,7%), and the most common type of benign lesion was vocal cord nodules 13(43,3%). Severe degree VHI-30 were most found 18(60,0%). The area of bilateral locations along the vocal cords had a significant relationship, with p-value of 0,040 (p<0,05), to the degree of VHI-30 when compared to the unilateral location of the anterior 2/3 of the vocal cords. Conclusion. The benign lesions’ position of bilateral along the vocal cord has a significant relationship to the severe degree of VHI-30